2020
DOI: 10.1093/conphys/coaa012
|View full text |Cite
|
Sign up to set email alerts
|

Faecal glucocorticoid metabolites as a measure of adrenocortical activity in polar bears (Ursus maritimus)

Abstract: Analysis of faecal glucocorticoid metabolites (FGMs) is frequently applied to assess adrenocortical activity in animal conservation and welfare studies. Faecal sample collection is non-invasive and feasible under field conditions. FGM levels are also less prone to circadian rhythms, episodic fluctuations and short acute stressors than glucocorticoid (GC) levels obtained from other matrices, for example blood or saliva. To investigate the suitability of FGM measurement in polar bears (Ursus maritimus), a specie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…Therefore, the assay presented here provides an efficient and modern alternative to measure endocrine stress responses in the brown bear. Interestingly, the cortisol that the EIA identified as the most suitable for brown bears in our results has also been shown as the most suitable for the closely related polar bear (Ursus maritimus; Hein et al 2020).…”
Section: Discussionsupporting
confidence: 64%
“…Therefore, the assay presented here provides an efficient and modern alternative to measure endocrine stress responses in the brown bear. Interestingly, the cortisol that the EIA identified as the most suitable for brown bears in our results has also been shown as the most suitable for the closely related polar bear (Ursus maritimus; Hein et al 2020).…”
Section: Discussionsupporting
confidence: 64%
“…The only way to determine a sex difference in the metabolism of cortisol would be to do a radio-label infusion in polar bears of both sexes, which has not been done to date. A sex difference in fecal cortisol metabolite concentrations was not observed in a recent study on zoo polar bears using a different polyclonal antibody, but the study included only five bears in total [41]. In contrast, Oskam et al, 2004 [42] found higher serum cortisol in adult females compared to adult males in samples collected from over 200 free-ranging polar bears in Norway.…”
Section: Sub-analyses Of Sexually Mature Adult Polar Bearsmentioning
confidence: 90%
“…While variability among individuals can reduce distinct patterns of fGCMs, predators, in general, show higher fGCMs during the breeding season than the non-breeding season. For example, female fishing cats ( Prionailurus viverinus ) and wolves exhibited higher fGCMs during winter (breeding season) compared to the non-breeding summer season [ 24 , 26 , 55 ], although no seasonal pattern was observed in polar bears [ 29 ] and tigers [ 6 ], suggesting that body size and/or food requirements may influence fGCM values. Seasonal GCM levels are modulated as a balance between required energy expenditure and available energy [ 1 ], but since the food available to our captive coyotes was constant, our fGCMs levels were likely not influenced by food availability or the demands of producing pups and were likely a stress response to an outside stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of GC and GCM levels at a broad temporal scale indicated that there were changes between the breeding and non-breeding seasons [ 1 , 24 , 25 , 26 , 27 ], with most mammalian species exhibiting an increase in GCs and GCMs during the reproductive season, late pregnancy [ 28 ], and lactation. While polar bears ( Ursus arctus ) in zoos did not exhibit seasonal differences [ 29 ], domestic cats ( Felis catus ; [ 30 ]), Amur wildcats ( Prionailurus bengalensis euptilura ; [ 31 ]), and Eurasian lynx ( Lynx lynx ; [ 32 ]) demonstrated a consistent increase in hair cortisol values during the mating season. The caracal ( Caracal caracal ), which is not a seasonal breeder (i.e., can breed any time of the year), exhibited a higher increase in hair cortisol during the autumn and lower during the spring [ 31 ].…”
Section: Introductionmentioning
confidence: 99%